2020
DOI: 10.48550/arxiv.2010.12555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak approximation and the Hilbert property for Campana points

Abstract: We study weak approximation and the Hilbert property for Campana points, both of importance in recent work on a Manin-type conjecture by Pieropan, Smeets, Tanimoto and Várilly-Alvarado. We show that weak weak approximation implies the Hilbert property for Campana points, and we exploit this to exhibit Campana orbifolds whose sets of Campana points are not thin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The hypothesis that the Campana points themselves are not thin is discussed by Nakahara and Streeter in [18]. The authors establish in [18,Theorem 1.1] a connection between thin sets of Campana points and weak approximation, in the spirit of Serre's arguments in [24,Theorem 3.5.7]. Combining this with [18,Corollary 1.4], it can be shown that this hypothesis holds for the orbifold we consider below.…”
Section: The Campana-manin Conjecturementioning
confidence: 83%
See 1 more Smart Citation
“…The hypothesis that the Campana points themselves are not thin is discussed by Nakahara and Streeter in [18]. The authors establish in [18,Theorem 1.1] a connection between thin sets of Campana points and weak approximation, in the spirit of Serre's arguments in [24,Theorem 3.5.7]. Combining this with [18,Corollary 1.4], it can be shown that this hypothesis holds for the orbifold we consider below.…”
Section: The Campana-manin Conjecturementioning
confidence: 83%
“…Then there is a thin set T of Campana O K,S -points such that Remark 2.8. The hypothesis that the Campana points themselves are not thin is discussed by Nakahara and Streeter in [18]. The authors establish in [18,Theorem 1.1] a connection between thin sets of Campana points and weak approximation, in the spirit of Serre's arguments in [24,Theorem 3.5.7].…”
Section: The Campana-manin Conjecturementioning
confidence: 99%
“…The authors establish in [10,Theorem 1.1] a connection between thin sets of Campana points and weak approximation, in the spirit of Serre's arguments in [15,Theorem 3.5.7]. Together with [10,Corollary 1.4], this implies that C is not itself thin. It remains to consider whether the second explanation above could hold.…”
Section: Introductionmentioning
confidence: 96%
“…(2) There is a thin set T ⊂ C of Campana points such that the removal of T from the count N 1 (B) reduces the leading constant to c PSTV-A . Recent work of Nakahara and Streeter in [10] tackles the question of when the set of Campana points corresponding to a log Fano orbifold (P n , D) can be a thin set. The authors establish in [10,Theorem 1.1] a connection between thin sets of Campana points and weak approximation, in the spirit of Serre's arguments in [15,Theorem 3.5.7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation